Antifungal Properties of Elephantopus scaber L. (Asteraceae) Against Crop Pathogenic Fungi - Nor Ain, binti Hussin; Mohamad Hasnul., B; Yeo, Freddy Kuok San (Universiti Malaysia Sarawak, (UNIMAS), 2016)
Harmful effect of synthetic fungicides towards environment and other organisms have become important issues nowadays. Research on the plant product to be developed as an alternative for synthetic fungicides has attracted interest of many scientists. The aim of this study is to determine the effect of antimicrobial properties of Elephantopus scaber L. from the family Asteraceae against six crop pathogenic fungi viz., Glomerella cingulata (Stoneman) Spauld. & H. Schrenk, Fusarium oxysporum Schltdl., Pyricularia oryzae Cavara, Fusarium solani (Mart.) Sacc., Pestalotiopsis sp., and Colletotrichum sp. Three different concentrations of E. scaber crude extract- 1%, 5% and 15%, were used in fungal growth inhibition test. At 15% (w/v) concentration, the mycelia growth of Colletotrichum sp., F. solani, and P. oryzae were significantly retarded. It indicates that the extract of E. scaber could potentially be used as a biofungicide.